(untitled) (Fiep Bulletin - online, 2011)
The objective is to know the opinion of professionals in physiotherapy and to correlate their opinions with the literature that discusses the subject. The research is based on qualitative methodology and techniques used were questionnaires and literature. The data were presented as tables and graphs, and treated statistically by the SPSS 16.0 statistical package. The data analysis adopted the descriptive statistics to characterize the sample through the distribution of frequency. For analysis of differences we used the chi-square. This study aims to determine the views of physiotherapists and see if it is in agreement with the evidence, since this is still a very controversial topic among healthcare professionals. The study found that 53.9% of physiotherapists believe that resistance training is beneficial to the health of teenagers and 46.1% believe the opposite.